2023
DOI: 10.3847/1538-4357/acc86a
|View full text |Cite
|
Sign up to set email alerts
|

The CGM2 Survey: Quenching and the Transformation of the Circumgalactic Medium

Abstract: This study addresses how the incidence rate of strong O vi absorbers in a galaxy’s circumgalactic medium (CGM) depends on galaxy mass and, independently, on the amount of star formation in the galaxy. We use Hubble Space Telescope/Cosmic Origins Spectrograph absorption spectroscopy of quasars to measure O vi absorption within 400 projected kpc and 300 km s−1 of 52 galaxies with M * ∼ 3 × 1010 M ⊙. The galaxies have redshifts 0.12 < z < 0.6, stellar ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 92 publications
(116 reference statements)
2
6
0
Order By: Relevance
“…Our results are also in agreement with a recent work of Tchernyshyov et al (2023), where the authors found that among galaxies with the same stellar or halo mass, O VI is more commonly detected in the CGM around star-forming galaxies than around passive galaxies. Tchernyshyov et al (2023) discussed two possible explanations for the detection of the O VI in the CGM around two passive galaxies from their sample, one was that the O VI is associated with another starforming interloping/neighboring galaxy, and the other was that galaxies that show O VI in their CGM were quenched more recently, and their CGM was still not transformed. Our results show that the former scenario might be more common.…”
Section: The Role Of Blue Ngssupporting
confidence: 93%
“…Our results are also in agreement with a recent work of Tchernyshyov et al (2023), where the authors found that among galaxies with the same stellar or halo mass, O VI is more commonly detected in the CGM around star-forming galaxies than around passive galaxies. Tchernyshyov et al (2023) discussed two possible explanations for the detection of the O VI in the CGM around two passive galaxies from their sample, one was that the O VI is associated with another starforming interloping/neighboring galaxy, and the other was that galaxies that show O VI in their CGM were quenched more recently, and their CGM was still not transformed. Our results show that the former scenario might be more common.…”
Section: The Role Of Blue Ngssupporting
confidence: 93%
“…The final range of stellar and halo masses for the sample are log 10 M å /M e ∼ 10.2-10.9 and log 10 M halo /M e ∼ 11.45-12.51, respectively. We note that a stellar mass of ≈10 10.5 M e is representative of L å galaxies, but also can be a transitional stellar mass in terms of sSFR, which is known to correlate with CGM properties in intermediate ionization states (Tchernyshyov et al 2023). However, by keeping the range of stellar and halo masses relatively small, we minimize the scatter due to these properties and enable a controlled examination of the role SMBHs and SFR play in shaping the Terrazas et al 2017), while stellar masses are accurate to about ∼50%.…”
Section: Sample Selectionmentioning
confidence: 91%
“…Other observational studies of cool gas around quiescent galaxies at z < 1 found similar results (Zahedy et al 2019;Chen et al 2020;Qu et al 2022). This work does not aim to answer the question of what causes galaxies to stop forming stars and what part the (cool) CGM plays in it (see Tchernyshyov et al 2023 for OVI-bearing gas). Our model can be applied to observations of quiescent galaxies in a future study.…”
Section: The Cool Cgm Reservoir: Depletion and Formationmentioning
confidence: 99%